Ex-ante Assessment of Drought Tolerant Bean Technology. A case study in the series: Economic Foresight for Understanding the Role of Investments in Agriculture for the Global Food System - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2016)
In this paper we apply an integrated biophysical and economic foresight modeling approach to investigate the impacts of climate change on the global agricultural economy, and the role that new crop technology could play in mitigating these impacts. In particular, we examine how the adoption of a drought tolerant common bean variety could serve as an adaptive measure in parts of the world where rising temperatures and decreasing rainfall are expected to place severe water stress on existing pulse farming systems over the period 2020 to 2050. Our study integrates the three mature, independently developed areas of crop, climate, and partial equilibrium economic modeling in order to accurately simulate climatic stress at the biophysical level, and then to register how this stress, as well as the measures taken to mitigate it, manifest at the socioeconomic level in terms of changes in supply and demand, international trade, land use, and food security. While the suite of models employed examines the global picture, our focus is on the Latin America and the Caribbean region (LAC) and Africa. The output suggests that, on average, adoption of drought tolerant common bean could mitigate climate change induced yield losses by 6% over the baseline variety. However, outcomes are nuanced in that yield impacts bear an ambiguous relation to impacts on cultivated area, production, net trade, and food security variables. Care must be taken when designing a climate change mitigating technology intervention at the country level so as to accommodate this nuance.